An autopsy study of hematolymphoid malignancies - Waghmare, Tejaswini P.; Prabhat, Daksha P.; Keshan, Pooja; Vaideeswar, Pradeep (International Journal of Research in Medical Sciences, 2019)
Background: Hematolymphoid malignancies (HLM) are primary cancers of blood, bone marrow and lymphoid organs associated with high mortality. Clinically undetected cases, diagnosed primarily at autopsy, are common. Methods: Cases of HLMs at autopsy performed in our hospital from 1st January 2009 to 30th June 2017 were analysed. Gross and microscopic findings at autopsy along with clinical parameters were studied. Special stains and immunohistochemistry (IHC) were performed wherever possible. Results: There were 49 cases of HLMs (0.98 %) among 4971 autopsies conducted during the study period, occurring predominantly in males (70 %). Fifteen (30.61 %) were primarily diagnosed at autopsy. There were 26 lymphomas and 19 leukemias; three patients had multiple myeloma and one patient had Langherhan cell histiocytosis. Non-Hodgkin’s lymphoma was the commonest (24 patients). Nine were diffuse large B-cell lymphoma; rare sub-types included angiotrophic lymphoma, post-renal lymphoproliferative disorder and hepatosplenic gamma-delta T-cell lymphoma. Among the 19 leukemias, majority were acute (13 cases) with seven cases of myeloid and six of lymphoid types. IHC was performed in 21 cases which aided the diagnosis. The commonest symptoms were fever (43%) and dyspnoea (37%). Splenomegaly (67%), hepatomegaly (61.2%) and lymphadenopathy (57.1%) were the most common autopsy findings. Infiltrations were seen in various organs; an acute myeloid leukemia (M6) had infiltration of the atrio-ventricular node. Conclusions: One-third cases in the present study were diagnosed at autopsy without any prior clinical suspicion thereby emphasizing on the relevance of autopsy in the current practice of pathology and further studies to improve accuracy of ante-mortem diagnosis.